The Development of a Vaccine Against Meningococcus B Using Reverse Vaccinology - Masignani, Vega; Pizza, Mariagrazia; Moxon, E. Richard (Frontiers in Immunology, 2019)
The discovery of vaccine antigens through whole genome sequencing contrasts with the classical hypothesis-driven laboratory-based analysis of microbes to identify components to elicit protective immunity. This radical change in scientific direction and action in vaccine research is captured in the term "reverse vaccinology". The complete genome sequence of a Neisseria meningitidis serogroup B isolate (MenB) was systematically analysed to identify proteins predicted to be secreted or exported to the outer membrane. Hundreds of genes coding for potential surface-exposed antigens, were amplified, cloned in expression vectors and used to immunise mice. Antisera against 350 recombinant antigens were analysed in a panel of immunological assays from which 28 were selected as potentially protective based on antibody dependent, complement mediated killing in the serum bactericidal assay (SBA). Testing of these candidate vaccine antigens on a globally representative strain collection of Neisseria species isolated from disease and carriage, indicated that no single component would be sufficient to induce broad coverage and that a “universal” vaccine should contain multiple antigens. The final choice of antigens to be included was based on cross-protective ability in SBA, and maximum coverage of the extensive antigenic variability of MenB strains. The resulting multivalent vaccine formulation selected consisted of three recombinant antigens (Neisserial Heparin Binding Antigen or NHBA, Factor H binding protein or fHbp and Neisseria Adhesin A or NadA). To improve immunogenicity and potential strain coverage, an outer membrane vesicle component obtained from the epidemic New Zealand strain (OMVNz) was added to the formulation to create a four component vaccine, called 4CMenB. A series of phase 2 and 3 clinical trials were conducted to evaluate safety and tolerability and to estimate the vaccine effectiveness of human immune responses at different ages, including concomitant vaccinations and lot-to-lot consistency. 4CMenB was approved in Europe in 2013 and introduced in the National Immunization Program in the UK starting from September 2015 in all newborns using a 2, 4 and 12 months schedule. The effectiveness against invasive MenB disease measured at eleven months after the study start and five months after the second vaccination was 83% and there have been no safety concerns.